Speed of Script: A Comparative Study between English and Nepali Medium School Students - Tiwari, Hari Prasad (AMC Journal (Dhangadhi), 2024)
Writing speed is one of the most essential requirements for higher academic purposes for the quality and quantity of student’s writing. It plays an important and significant role in every one’ life. This research utilized a cross-sectional survey design to compare writing speeds in English and Nepali among students in the District of Banke, focusing on three English Medium School(s) (EMS) and three Nepali Medium School(s) (NMS). The researcher employed purposive sampling technique to select the sample of 30 students from each school. The sample included an equal number of boys and girls from both schools resulting in a total of 60 students. Data collection involved administering a standardized writing speed test under controlled conditions. The speeds were measured in words per minute (w/m) for both languages. Analysis of the data revealed that English writing speeds generally exceeded Nepali, with mode values of 29.07 w/m for English and 24.88 w/m for Nepali. The median for English was 27.20 w/m, and for Nepali, it was 20.72 w/m, while the arithmetic means were 24.36 w/m for English and 20.2 w/m for Nepali. The comparative analysis showed a higher proportion of students performing above average in English compared to Nepali.